Islamic Values-Based Education Management Strategy at MI Raudhatul Hasanah Tangerang - Iqbal, Muhammad (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Contemporary Islamic educational institutions face complex dynamics that necessitate a reformulation of strategic management paradigms grounded in Islamic values to achieve institutional excellence while upholding spiritual authenticity. This study aims to analyze, evaluate, and formulate an effective Islamic value-based education management strategy at MI Raudhatul Hasanah Tangerang, as well as identify the determining factors that affect the successful implementation of the strategy. The study employed a qualitative method with an interpretive descriptive approach, utilizing an ethnographic case study. This involved in-depth interviews with eight key informants, participatory observation over four months, and documentation analysis using purposive sampling techniques. The study's findings identified four integrated strategic dimensions: strategic planning based on shura-hikmah, resource organization based on the principle of tanzhim-justice, transformational leadership inspired by the example of the Prophet PBUH, and holistic performance evaluation through the muhasabah-muraqabah approach. The novelty of the research led to the development of the Islamic Education Management Tetrahedron Model (TMPI). This comprehensive framework integrates spiritual, managerial, and operational dimensions into a coherent system. This empirical research offers significant implications for the development of superior and sustainable Islamic education management systems, providing strategic recommendations for the creation of technology-based management information systems and managerial capacity-building centers for Islamic education leaders to ensure the scalability and sustainability of the model.